Growth hormone is protective against acute methadone-induced toxicity by modulating the NMDA receptor complex. (17th December 2016) - Nylander, Erik; Grönbladh, Alfhild; Zelleroth, Sofia; Diwakarla, Shanti; Nyberg, Fred; Hallberg, Mathias
Graphical abstract: Highlights: Methadone causes cellular toxicity in cortical cell cultures. Growth hormone protects cells against methadone-induced toxicity. A protective mechanism of growth hormone is proposed. Abstract: Human growth hormone (GH) displays promising protective effects in the central nervous system after damage caused by various insults. Current evidence suggests that these effects may involve N -methyl-d -aspartate (NMDA) receptor function, a receptor that also is believed to play a role in opioid-induced neurotoxicity. The aims of the present study were to examine the acute toxic effects of methadone, an opioid receptor agonist and NMDA receptor antagonist, as well as to evaluate the protective properties of recombinant human GH (rhGH) on methadone-induced toxicity. Primary cortical cell cultures from embryonic day 17 rats were grown for 7 days in vitro . Cells were treated with methadone for 24 h and the 50% lethal dose was calculated and later used for protection studies with rhGH. Cellular toxicity was determined by measuring mitochondrial activity, lactate dehydrogenase release, and caspase activation. Furthermore, the mRNA expression levels of NMDA receptor subunits were investigated following methadone and rhGH treatment using quantitative PCR (qPCR) analysis. A significant protective effect was observed with rhGH treatment on methadone-induced mitochondrial dysfunction and in methadone-induced LDH release. Furthermore, methadone significantly increased caspase-3 and -7 activation but rhGH was unable to inhibit this effect. The mRNA expression of the NMDA receptor subunit GluN1, GluN2a, and GluN2b increased following methadone treatment, as assessed by qPCR, and rhGH treatment effectively normalized this expression to control levels. We have demonstrated that rhGH can rescue cells from methadone-induced toxicity by maintaining mitochondrial function, cellular integrity, and NMDA receptor complex expression.